Pattern and Severity of Psoriasiform Eruptions in Patients with Inflammatory Bowel Diseases, Arthritis or Skin Inflammatory Disorders Treated with TNF-alpha Inhibitors - Anne-Sophie Darrigade; Brigitte Milpied; Marie-Elise Truchetet; Thierry Schaeverbeke; David Laharie; Frank Zerbib; Marie Beylot-Barry; Thomas Jouary; Alain Taïeb; Khaled Ezzedine; Julien Seneschal (Medical Journals Sweden, 2017)
Psoriasiform eruptions are a classical adverse skin reaction of tumour necrosis factor (TNF)-α inhibitors. The aim of this study was to identify the association between the severity or pattern of psoriasiform reactions and the underlying disease. A retrospective study was conducted between January 2012 and May 2015. Adult patients who developed psoriasiform eruptions whilst being treated with TNFα inhibitors were included. For each patient, 3 independent blinded dermatologists graded twice the severity of the lesions according to 6 clinical psoriasiform eruption types. Inter- and intra-individual kappa tests were performed to evaluate the robustness of the scoring system. The association between severity score levels or the pattern of reactions and the underlying disease was assessed. The severity scoring system showed good inter- and intra-observer reproducibility. Women patients treated with TNFα inhibitors for inflammatory bowel diseases showed a higher risk of developing severe reactions with scalp and skin-fold involvement.